Assessing the Nursing Knowledge and Practices in Premature Feeding in Premature Units - Baydaa Yahya, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: ٨ descriptive study has been conducted in the premature baby unit in Al-Khansaa' and Al-Batoolhospitals for maternity and children in Mosul city to assess knowledge and practice of the nursing staff in thecaring of premature infants. A descriptive study has been conducted in the premature baby unit in Al-Khansaa'and Al-Batool hospitals for maternity and children in Mosul city to assess knowledge and practice of the nursingstaff in the caring of premature infants.Methodology: the data were collected by using knowledge assessment and practice measurement tool.Results: the results of the study show that high percentages (about 40%) of the staff who work in the prematurebaby units are of the young age group. It has also been found that the ratio of 2/1 of female workers is higherthan male workers in such units. Highly significant differences have been found by measuring the average ofknowledge and practice in general with regard to theoretical Mean. The study shows that there are significantdifferences (